The Influence Factors of Students Conginitive Process in Writing - Rizky Ummi Thahirah Nasution; Herika Dalimunthe; Dinda Sundana; Yani Lubis (Lembaga Pengembangan Kinerja Dosen, 2024)
The Chinese nation is a developed nation and has a variety of unique cultures and customs. Not only that, the physical characteristics and lifestyle of this nation have attracted the attention of a number of nations in the world, especially western nations. So in this study, researchers try to dig deeper into gender stereotypes against the Chinese nation through the film Mulan (2020). Stereotypes exist because of the hegemony of a gender perspective towards Eastern nations, including the Chinese nation. The existence of scientific research activities on Eastern nations and writing activities has made a number of people have their own perspective on Eastern nations which are dominated by negative views. Therefore, by using a descriptive qualitative research method, researchers can carefully process data and analyze descriptively the research topic, namely what stereotypes are present in the film Mulan (2020) towards the Chinese nation. Both in terms of physical characteristics and patterns of social life. Assisted by a subjective interpretive approach, researchers try to use reason and reason to examine stereotypes in the film Mulan (2020) to obtain conclusions from research results such as stereotypes against the Chinese nation in terms of ideological beliefs that still believe in ancestors who are considered mystical, mindset which are still traditional so that there is no gender equality.